Periodic waves in the lower thermosphere observed by OI630 nm airglow images - I. Paulino; A. F. Medeiros; S. L. Vadas; C. M. Wrasse; H. Takahashi; R. A. Buriti; D. Leite; S. Filgueira; J. V. Bageston; J. H. A. Sobral; D. Gobbi (Annales Geophysicae, 2016)
Periodic wave structures in the thermosphere have been observed at São João do Cariri (geographic coordinates: 36.5° W, 7.4° S; geomagnetic coordinates based on IGRF model to 2015: 35.8° E, 0.48° N) from September 2000 to November 2010 using OI630.0 nm airglow images. During this period, which corresponds to almost one solar cycle, characteristics of 98 waves were studied. Similarities between the characteristics of these events and observations at other places around the world were noted, primarily the spectral parameters. The observed periods were mostly found between 10 and 35 min; horizontal wavelengths ranged from 100 to 200 km, and phase speed from 30 to 180 m s−1. These parameters indicated that some of the waves, presented here, are slightly faster than those observed previously at low and middle latitudes (Indonesia, Carib and Japan), indicating that the characteristics of these waves may change at different places. Most of observed waves have appeared during magnetically quiet nights, and the occurrence of those waves followed the solar activity. Another important characteristic is the quasi-monochromatic periodicity that distinguish them from the single-front medium-scale traveling ionospheric disturbances (MSTIDs) that have been observed previously over the Brazilian region. Moreover, most of the observed waves did not present a phase front parallel to the northeast–southwest direction, which is predicted by the Perkins instability process. It strongly suggests that most of these waves must have had different generation mechanisms from the Perkins instability, which have been pointed out as being a very important mechanism for the generation of MSTIDs in the lower thermosphere.